Plugin Problem - # 2

Jason76

Senior Member
Joined
Oct 19, 2012
Messages
1,180
\(\displaystyle f(x) = 4x^{3} + 9x^{2} - 54x + 8 \)

\(\displaystyle f(-\dfrac{3}{4}) = 4(-\dfrac{3}{4})^{3} + 9(-\dfrac{3}{4})^{2} - 54( -\dfrac{3}{4}) + 8 = \dfrac{273}{8}\) :confused: This is wrong on the computer.
 
Last edited:
\(\displaystyle f(x) = 4x^{3} + 9x^{2} - 54x + 8 \)

\(\displaystyle f(-\dfrac{3}{4}) = 4(-\dfrac{3}{4})^{3} + 9(-\dfrac{3}{4})^{2} - 54( -\dfrac{3}{4}) + 8 = \dfrac{273}{8}\) :confused:
What were the instructions? What are you doing? What is your question?
 
Top